Localisation of asterion and its relationship to transverse and sigmoid venous sinuses - Tanat Tabtieang; Sirikorn Dokthien; Poramed Amorntodsapornpong; Thanasil Huanmanop; Sithiporn Agthong; Vilai Chentanez (Folia Morphologica)
BACKGROUND: The asterion has been recognised as the external skull landmark for localisation of the transverse and sigmoid sinus junction (TSJ). This study aimed to localise the asterion using the intersection of the Frankfort horizontal plane (FHP) line and a vertical line from the mastoid tip, and to determine its relationship with the transverse and sigmoid sinuses. MATERIALS AND METHODS: Distances from the asterion to the FHP and vertical line were measured on 200 dry skulls (100 males and 100 females). In addition, 48 cadavers (24 males and 24 females) underwent asterion drilling, and the relationship with the transverse and sigmoid sinuses was recorded. RESULTS: In most skulls, the asterion was superior to the FHP line, with average distances of 0.5 ± 0.3 cm on both sides. Distances to the vertical line were 3.7 ± 0.4 cm and 3.9 ± 0.4 cm for the left and right sides, respectively. These distances were statistically significant different between sides, but not between sexes. The location of the asterion was mainly over the TSJ (54%) and transverse sinus (42%). The accuracy of a predictive method was evaluated in an additional 10 cadavers. The predicted positions were located with distances ranging from 0 to 1.3 cm in the horizontal plane (0.4 ± 0.4 cm), and 0 to 0.7 cm in the vertical plane (0.3 ± 0.2 cm) from the asterion. CONCLUSIONS: This study confirms an anatomical relationship between the asterion and TSJ including the transverse sinus. We have also revealed an alternative method for localising the asterion.